Quantum transport of Au-S-S-Au nanoscale junctions - SANVITO, STEFANO (My University, 2012)
Transport in S2 molecules sandwiched between Au electrodes is investigated with a combination of density functional theory and the non-equilibrium Green?s function method. We consider four different configurations and find that their conductances are related to the details of the bonding geometry. When S2 connects to pyramidal-shaped electrodes at the top site, the transmission is governed by a resonance and is strongly affected by the bias. In contrast, the transport of the remaining three configurations is through several closely spaced broad molecular orbitals, and the transmission coefficient is almost flat around the Fermi level.
PUBLISHED
Keywords: Nanoelectronic devices; bonds (chemical); density functional theory; Nanoscience & Materials